Monitoring Monitoring Angka Coliform dan Eschercia Coli Pada Air Minum Isi Ulang Sebagai Bioindikator Pencemaran - Hoetary Tirta Amallia (Biota, 2020)
One of the very needed natural resources on our planet is water. A total of 70% of the Earth's surface is water utilized for human development such as drinking, irrigation and cultivating fish. Contaminated water will have a bad effect on all living creatures and their environment [7]. Sources of water pollution can be derived from manusi stool containing coliform bacteria. The research purposes will be monitoring colifom number and Escherichia coli on some samples of drinking water as a bioindicator of drinking water pollution considering the higher the population consuming drinking water refill. This resource is pure resource experiment that use design of resource descriptive analitic. The data obtained will be displayed in the frequency distribution table to see the figure of coliform and E.coli in refill drinking water. From the results of this study, of 20 samples of drinking water refill there were 14 unqualified samples where the coliform figures exceeded quality standards. And 5 positive samples of E. Coli bacteria